Microbial taxonomic, nitrogen cycling and phosphorus recycling community composition during long-term organic greenhouse farming. Issue 5 (30th March 2019) - Ding, Guo-Chun; Bai, Mohan; Han, Hui; Li, Huixiu; Ding, Xiaoyan; Yang, Hefa; Xu, Ting; Li, Ji
ABSTRACT: Understanding the interplay between the farming system and soil microbiomes could aid the design of a sustainable and efficient farming system. A comparative greenhouse experiment consisting of organic (ORG), integrated (INT) and conventional (CON) farming systems was established in northern China in 2002. The effects of 12 years of organic farming on soil microbiomes were explored by metagenomic and 16S rRNA gene amplicon sequencing analyses. Long-term ORG shifted the community composition of dominant phyla, especially Acidobacteria, increased the relative abundance of Ignavibacteria and Acidobacteria Gp6 and decreased the relative abundance of Nitrosomonas, Bacillus and Paenibacillus . Metagenomic analysis further revealed that relative abundance of ammonia oxidizing microorganisms ( Bacteria and Archaea ) and anaerobic ammonium oxidation bacteria decreased during ORG. Conversely, the relative abundance of bacteria-carrying periplasmic nitrate reductases ( napA ) was slightly higher for ORG. Long-term organic farming also caused significant alterations to the community composition of functional groups associated with ammonia oxidation, denitrification and phosphorus recycling. In summary, this study provides key insights into the composition of soil microbiomes and long-term organic farming under greenhouse conditions. Abstract : Long-term organic system shifted the community composition of dominant phyla, increased the relative abundance of Ignavibacteria and Acidobacteria Gp6 and decreased the relative abundance of Nitrosomonas, Bacillus and Paenibacillus.